Gambaran Pengelolaan Program Bantuan Operasional Kesehatan (BOK) di Dinas Kesehatan Kabupaten Jember - Didimus Adiwijaya; Eri Witcahyo; Abu Khoiri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Health Operational Assistance (HOA) is a program aimed at funding promotive and preventive activities of national priority health programs. The absorption of the HOA budget for the 2021-2024 fiscal years was 24.21%, 69.43%, 80.81%, and 85.7%, respectively. This absorption isn’t yet considered good, with a percentage of <90% and impacting the reduction in the proposed allocation for the following fiscal year. This study used descriptive research. The respondents were the Head of the Public Health Division, the Head of the Planning and Finance Subdivision, and Public Health staff. Primary data for this study were obtained through interviews, while secondary data included the HOA Realization Report, the Decree of the Head of the Health Office concerning the HOA Management Team, and the Technical Guidelines for the Use of HOA Funds for 2021-2024. Data analysis used descriptive analysis. The results showed that the planning process used a bottom-up proposal method. The Health Office used the Decree of the Head of the Health Office concerning the Health Office's HOA Management Team in 2023. Implementation obstacles included the late determination of the Budget Implementation Document (BID) in March, which delayed activity implementation. Supervision was carried out by the Health Office, the Supreme Audit Agency (SAA), and the Regional Financial and Asset Management Agency (RFAM), as well as reviews by the Ministry of Health's Inspectorate General. This research suggests that the Health Office can further optimize program implementation, particularly for activities with low budget absorption, by improving cross-sectoral coordination and building harmonization with the legislature.